Tripartite Svetlichny test with measurement dependence - Li, Run-Ze; Li, Dan-Dan; Wu, Sheng-Yao; Qin, Su-Juan; Gao, Fei; Wen, Qiao-Yan (Frontiers in Physics, 2024)
Bell test, as an important method for detecting nonlocality, is widely used in device-independent quantum information processing tasks. The security of these tasks is based on an assumption called measurement independence. Since this assumption is difficult to be guaranteed in practical Bell tests. It is meaningful to consider the effect of reduced measurement independence (i.e. measurement dependence) on Bell tests. Some researches have shown that nonlocality can be detected even if measurement dependence exists. However, the relevant results are all based on bipartite Bell tests, the results for multipartite cases are still missing. In this paper, we explore this problem in tripartite Svetlichny test. By considering flexible lower and upper bound on the degree of measurement dependence, we obtain the relation among measurement dependence, guessing probability and the maximal value of Svetlichny inequality. Our results reveal the case in which genuine nonlocality is not exist, at this point the outcomes of Bell test cannot be applied in device-independent quantum information processing tasks.